ArgR regulates motility and virulence through positive control of flagellar genes and inhibition of diguanylate cyclase expression in Aeromonas veronii - Zucheng Wang; Yanqiong Tang; Hong Li; Juanjuan Li; Xue Chi; Xiang Ma; Zhu Liu (Communications Biology)
Abstract Flagella are essential for biofilm formation, adhesion, virulence, and motility. In this study, the deletion of argR resulted in defects in flagellar synthesis and reduced motility, nevertheless, the underlying mechanism by which ArgR regulated bacterial motility remained unclear. ChIP-Seq and RNA-Seq analysis revealed that ArgR regulated the expression of flagellar genes, concluding two-component system flrBC and multitudinous flagellar structure genes. Specifically, ArgR bound to the ARG box in the flrBC promoter, positively regulating flrBC expression, which in turn promoted flagellar synthesis and enhanced motility. Additionally, in the absence of arginine, ArgR inhibited the expression of diguanylate cyclase, leading to reduced c-di-GMP levels, thereby alleviating its inhibitory effect on motility. Thus, ArgR coordinated two distinct pathways to regulate flagellar assembly and motility, ultimately affecting adhesion, virulence, and biofilm formation. In summary, this study elucidates the molecular mechanism by which ArgR regulates motility, highlighting its crucial role in bacterial virulence and offering new insights for the prevention and control of pathogenic bacteria.